Indonesian National Police Participation in Literacy Programs for Border and General Communities - Putra, Aman Dhito Krishardi; Maulana , Daffa Iqbal; Hutadjulu, Christopher Ramos; Sarmiko, Jerico Tsar; Parembang, Keyko Septian (Indonesian National Police Academy, 2025)
This article reviews the Indonesian National Police's (Polri) participation in literacy programs targeting both border communities and the general population. Through a comprehensive literature review methodology, this study examines the scope, implementation strategies, challenges, and impacts of these initiatives within the framework of community policing. The review synthesizes findings from academic articles, official reports, and policy documents to assess how literacy programs contribute to national security, community empowerment, and police-community relations. Results indicate that Polri's literacy initiatives encompass digital literacy campaigns, human rights education, and community policing training, particularly in vulnerable border areas and underserved populations. These programs have demonstrated positive impacts on community engagement, crime prevention capabilities, and public trust in law enforcement. However, significant challenges persist, including resource constraints, operational demands in remote areas, and the need for sustained community engagement. The study concludes that literacy programs represent a crucial component of Indonesia's comprehensive security strategy, requiring continued investment, stakeholder collaboration, and adaptive implementation approaches. Recommendations include expanding digital literacy initiatives, strengthening partnerships with international organizations, and developing robust evaluation frameworks to measure program effectiveness.